Optimal taxation of externalities interacting through markets: A theoretical general equilibrium analysis - Xiaolin Ren; Don Fullerton; John B. Braden (Center for Economic Studies and ifo Institute (CESifo), 2010)
This study develops a theoretical general equilibrium model to examine optimal externality tax policy in the presence of externalities linked to one another through markets rather than technical production relationships. Analytical results reveal that the second-best externality tax rate may be greater or less than the first-best rate, depending largely on the elasticity of substitution between the two externality-generating products. These results are explored empirically for the case of greenhouse gas from fossil fuel and nitrogen emissions associated with biofuels.
Keywords: D50; H23; Q58; 330; second-best tax; multiple externalities; biofuel; GHG emissions; nitrogen leaching; Internalisierung externer Effekte; Optimale Besteuerung; Second Best; Biokraftstoff; Treibhausgas; Stickoxid; Umweltbelastung; Allgemeines Gleichgewicht; Theorie